The level of platelets in patients operated for a fracture of the neck of the femur - Magdalena Babuśka-Roczniak; Magdalena Wojtanowska-Kaczka; Mateusz Kowalski; Marta Skalik; Oliver Racz; Elżbieta Oliwko; Wojciech Roczniak (Kazimierz Wielki University, 2021)
Admission. Treatment of hip fractures is one of the most serious challenges for musculoskeletal traumatology, as these fractures occur mainly in the elderly. Despite the fact that modern traumatology has reached a high level, femoral neck fractures are still a very big problem among societies.             The purpose of the study was an assessment of the level of platelets in patients treated with surgery for a fracture of the neck of the femur.             Material and method. The research was conducted in December 2019 in one of the trauma and orthopedic wards in Upper Silesia. The study included 35 patients aged 48-78 years treated surgically due to a hip fracture. All obtained data on patients come from medical records.             Results. The analysis showed that 8 of the 35 patients included in the study had a decrease in the level of platelets 24 hours after the surgical treatment of a hip fracture. One week after the surgery, the level of platelets was normal.             Conclusions. A relationship has been demonstrated between the level of platelets and surgical treatment of a fracture of the femoral neck. A significant drop in platelets was noticed in 23% of the subjects 24 hours after the surgery and their normal value was reached a week later. The problem requires further observation and research.